2017
DOI: 10.1002/hyp.11381
|View full text |Cite
|
Sign up to set email alerts
|

The importance of choosing precipitation datasets

Abstract: Precipitation data are important for hydrometeorological analyses, yet there are many ways to measure precipitation. The impact of station density analysed by the current study by comparing measurements from the Missouri Mesonet available via the Missouri Climate Center and Community Collaborative Rain, Hail, and Snow (CoCoRaHS) measurements archived at the program website. The CoCoRaHS data utilize citizen scientists to report precipitation data providing for much denser data resolution than available through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Although both the meteorological stations are observed with the manually standard process in the standard field with grass land cover, the local factors such as terrain and wind are still different to considered and corrected. Many different studies [62][63][64], among many, have concluded that automated gauges have many errors associated with them, among which some errors as high as 80% under extremely detrimental conditions.…”
Section: Reasons For Different Performance Of Ree Productsmentioning
confidence: 99%
“…Although both the meteorological stations are observed with the manually standard process in the standard field with grass land cover, the local factors such as terrain and wind are still different to considered and corrected. Many different studies [62][63][64], among many, have concluded that automated gauges have many errors associated with them, among which some errors as high as 80% under extremely detrimental conditions.…”
Section: Reasons For Different Performance Of Ree Productsmentioning
confidence: 99%
“…Furthermore, results demonstrate the issues with analyzing QPE from a single gauge, explaining why the Community Collaborative Rain, Hail, and Snow Network (Kelsch, 1998;Cifelli et al, 2005;Reges et al, 2016) or other densely gauged networks (e.g., the Hydrometeorological Automated Data System, HADS; and the Meteorological Assimilation Data Ingest System, MADIS) tend to be more utilized since results have shown that measurements or qualitycontrolled techniques made by these organizations, especially CoCoRaHS (Community Collaborative Rain, Hail and Snow Network), are significantly more accurate than rain gauges (Simpson et al, 2017), especially for convective events (Moon et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is a primary input when developing different climate and weather numerical models. Long enough records of this variable are necessary to carry out a wide range of studies in many water-related disciplines, such as water resources management, extreme events analysis, climate change, among others (Simpson et al, 2017;Tabari, 2020).…”
Section: Introductionmentioning
confidence: 99%